Digital Transformation of Borrowing System and Returning Medical Equipment - Dian Eka Resty; Rr. Tutik Sri Hariyati; Tuti Afriani; Sudaryati Sudaryati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Medical equipment is an important element in health services, however, inadequate maintenance and management leads to a decrease in the efficiency and effectiveness of equipment operations. The purpose of this study was to determine the effectiveness of a digital equipment loan and return system. The method used is a pilot project with the Kurt Lewin approach. The unfreezing stage was carried out by identifying problems through interviews, observations, questionnaires to inpatient nurses at X Hospital. The movement stage, the implementation of the plan of action (plan of action) prepared with the hospital. The refreezing stage cannot be carried out because the implementation process is still ongoing. The results of the implemented solution are the use of G-forms as a medium for recording the borrowing and returning of medical devices between inpatient rooms and testing web applications. Recommendations for RS X are the establishment of regulations for borrowing and returning medical devices, socialisation of web applications as a medium for borrowing and returning medical devices, the need for logistics training for nursing staff.